Medición y Evaluación en Comunicación Estratégica. Caso de Estudio Programa ENES de la SENESCYT. - Bonilla Rodríguez, Miriam del Rocío (2014)
This study was conducted in the SENESCYT, mainly in the ENES program (National Examination for Higher Education), focused on managing the assessment and measurement of Strategic Communication. The primary objective of the study was to analyze the process of strategic communication planning from a model for the measurement and evaluation, in this case, the model “Communication Management Bridge”, Alvarez Nobell. The study methodology using interviews spanned the communications coordinator and official spokeswoman ENES program during 2013 rose addition information from the documents and records SENESCYT. As a result it was observed that handles communication SENESCYT for all Secretariats and programs centrally, without strategic planning and from communicative actions that respond to the needs of each project; however, do not have evaluation processes of communication achieved accomplishments, performing qualitative and highly empirical assessment of external communication